Pengaruh Lingkungan Keluarga, Sikap Dan Pendidikan Kewirausahaan Terhadap Minat Berwirausaha - Prasetya, Hendra; Ariska, Ricy Angga (Universitas Of Surakarta, 2021)
This study aims to determine the significance of the influence of the family environment, attitudes and entrepreneurship education partially on the interest in entrepreneurship in students of the management study program, Faculty of Economics and Business, Wijaya Kusuma University, Surabaya. The research variables studied were one dependent variable, namely interest in entrepreneurship, and three independent variables, namely family environment, attitudes, and entrepreneurship education. The population is students from the economics and Business Faculty, Wijaya Kusuma University, Surabaya while the determination of the sample is based on purposive sampling with the following criteria: 1)a student of management studies program; 2)already or currently taking entrepreneurship courses, and 3)his parents or family are entrepreneurs. The number of samples studied was 100 respondents. The analysis technique uses multiple linear regression analysis while the hypothesis is tested by t-test. The results of hypothesis testing indicate that the t-count value is greater than the t-table with the significance value of less than 0,05, so the family environment, attitudes, and entrepreneurship education partially have a significant interest in entrepreneurship in management study program student, Faculty of Economics and Business, Wijaya Kusuma University, Surabaya. So that interest in entrepreneurship among students continues to grow, students should be in an environment related to entrepreneurial activities, instilling an entrepreneurial attitude among students and periodically the faculty adjusts the entrepreneurship course material with current conditions.